The Influence Of Product Quality and Online Shopping Experience on The Purchase Decision of HMNS Local Perfume Products Among Generation Z - Tias Andarini Indarwati; Cahyani Dewi Lisa Prastiya (International Journal of Social, Economic, and Business, 2025)
The expanding beauty industry and increased perfume consumption among Generation Z underscore the importance of further examining their purchase behavior. This study aims to identify the influence of product quality and online shopping experience on purchasing decisions. The population in this study is Generation Z individuals who have purchased HMNS local perfume products online, with a sample size of 200 respondents. Using multiple linear regression analysis, the findings reveal that both product quality and online shopping experience have a significant effect on purchasing decisions, with product quality exerting the most dominant influence. This indicates that Generation Z places high importance on product quality when making purchase choices. The practical implication of this study suggests that HMNS should continue to enhance product quality and provide a seamless online shopping experience to support consumer decision-making and strengthen brand competitiveness.